Pelaksanaan Program Pembinaan Akhlak Dalam Pengendalian Perilaku Anak Didik Smp Islam Terpadu (It) Al-Karim - Puput Anggraini; Hidayat (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Implementation of a moral development program in controlling the behavior of students at AL-Karim Integrated Islamic Middle School (IT)." The aim of this research is to determine the implementation of the program and control of students' behavior from knowledge, experience and habituation. This type of research is field research with a qualitative approach. There are two data sources used, namely primary and secondary data sources. Data collection techniques through observation, interviews and documentation. Data analysis techniques are data reductions (data reduction), data display (data presentation), data verification (drawing conclusions). The results of the research show that the implementation of the program and controlling students' behavior in developing morals through extracurricular activities at AL-Karim Integrated Islamic Middle School (IT) has been created very well, this is proven by six students being said to be very good and one student being said to be good. This proves that the moral development of students through extracurricular activities at AL-Karim Integrated Islamic Middle School (IT) is very good. There are supporting and inhibiting factors in moral development. Supporting factors are, 1) The existence of a vision, mission 2) The existence of appropriate and mature planning 3) Competent and experienced educators 4) There is good management. 5) The existence of facilities and infrastructure. Inhibiting factors are, 1) disciplined attitudes, for example when praying there are still students who are not serious 2) midday prayers in congregation are sometimes not carried out due to lack of clean water.Keywords: Program, Morals, Behavior